Politics and Democracy in Nigeria: A Critical Examination and Analysis of the Use and Mis-use of Money in Elections - Salami, Adebayo T (Green University Review of Social Sciences, 2022)
How important is money to politics? In other words, what important role does money play in politics? What explains the role of money in politics, and further its importance? How can the importance attached to the role of money in politics be scholarly demonstrated, and by what empirical yardsticks of presentations and analyses? The paper, with special focus on what it calls: “…the use and mis-use of money in politics”, seeks to, within the context of the Nigerian political system, investigate and analyze the role of money in politics. The research methodology combines historical cum analytical mode of data sourcing with evidence-based investigations organized around important thematic and sub-thematic issues and problems in the sub-field of psephology. The methodology, further advanced within the perspective of provocative and inquisitive scholarship, raises fundamental questions that were considered useful for the interrogation of the subject matter and the consequent organization of the accompanying research. For instance, how are money, politics and power related, and within what scholarly template of critical social science inquiry? Which influences the other and to what extent and degree of consequences and relationships? How can the relationships between and among these be measured and by what indices and criteria of strict scientific measurement and evaluation? The answers to the questions provide important findings/information with respect to the future of democracy in Nigeria when approached from the perspective of the cost of elections which tend to favour the highest bidders, the “money-bags” as called. The fact that the future of democracy becomes endangered under the circumstance, recommendations are consequently made on how to mitigate the cost of elections and further enhance democratic political practice. Green University Review of Social Sciences Dec 2021; 7(1-2): 35-64